Relations in the Communication Networks Centrality for Disaster Risk Reduction - Damayanti Wardyaningrum (Universitas Muhammadiyah Yogyakarta, 2019)
The purpose of the research is for capturing communications network of the people in the natural disaster area of mount Merapi in Central Java. Dusun Kalitengah kudul is one of the worst vilages when merapi erupstion in 2010. This location has been acknowledgeed as the red zone but the local people dicided to stay since the historical and economic reason. Focus of the research is to identify the centralisation of communication network regarding the evacuation exercise as preventive action in disaster moment. The research use post positivist method with data survey and interview for data collecting. The research found that the a network is low centralized in which relations are focused on some actors. In this decentralized network, conversely, are those in which power and control of information and resources are diffuse and spread over a number of actor. The actors in central positions are consist of common local people, people in social structure, local government, people from university and volunteers. The messages flow in communication network are the relation of people regarding the evacuation process, the location for evacuation, and the need of accommodation during disaster. The spread centralization to many actors is very potential for capacity community building in disaster moment.